Association of lipoprotein lipase gene with coronary heart disease in Sudanese population - Muzamil M. Abdel Hamid; Safa Ahmed; Awatif Salah; Etayeb M.A. Tyrab; Lemya M. Yahia; Elbagire A. Elbashir; Hassan H. Musa (Springer, 2019)
Cardiovascular disease is stabilizing in high-income countries and has continued to rise in low-to-middle-income countries. Association of lipid profile with lipoprotein lipase gene was studied in case and control subject. The family history, hypertension, diabetes mellitus, smoking and alcohol consumption were the most risk factors for early-onset of coronary heart disease (CHD). Sudanese patients had significantly (P < 0.05) lower TC and LDL-C levels compared to controls. Allele frequency of LPL D9N, N291S and S447X carrier genotype was 4.2%, 30.7% and 7.1%, respectively. We conclude that lipoprotein lipase polymorphism was not associated with the incidence of CHD in Sudan.